2017
DOI: 10.1053/j.gastro.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Colorectal Cancer in Patients With Multiple Serrated Polyps and Their First-Degree Relatives

Abstract: The risk of CRC in patients with multiple serrated polyps who do not meet the criteria for serrated polyposis, and in their first-degree relatives, is similar to that of patients diagnosed with serrated polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
(36 reference statements)
1
25
0
Order By: Relevance
“…53,54 Recent data suggests once the colon is cleared, follow-up can be safely deferred to 2 years. 55,56 The risk for patient who are first-degree relatives of patients with SPS also appears elevated between 3-to 5-fold compared to the general population 51,57,58 and screening colonoscopy is recommended for this group, with subsequent colonoscopies determined by polyp burden. Surveillance should then be performed every 5 years if no polyps are found.…”
Section: Serrated Polyposis Syndrome Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Recent data suggests once the colon is cleared, follow-up can be safely deferred to 2 years. 55,56 The risk for patient who are first-degree relatives of patients with SPS also appears elevated between 3-to 5-fold compared to the general population 51,57,58 and screening colonoscopy is recommended for this group, with subsequent colonoscopies determined by polyp burden. Surveillance should then be performed every 5 years if no polyps are found.…”
Section: Serrated Polyposis Syndrome Surveillancementioning
confidence: 99%
“…A recent paper that looked at patients with multiple serrated polyps and adenomas, not quite meeting the criteria for SPS also noted that their risk for CRC was equivalent to patients who met the WHO definition of SPS, and that their first-degree relatives also had an elevated risk of CRC, comparable to the risk for first-degree relatives of SPS patients. 58…”
Section: Serrated Polyposis Syndrome Surveillancementioning
confidence: 99%
“…Considering the limited amount of supporting evidence, studies questioning the durability of the WHO criteria will improve future guidelines. Because of the lack of prospective studies, for now we will have to rely on retrospective studies such as the study of Egoavil et al 5 Although biased, this study perfectly showed that the WHO criteria draw a firm line within a disease that seems to be more of a continuum. However, the authors' recommendation to expand SPS surveillance guidelines to all MSP patients and their first-degree relatives seems reversed reasoning and would unnecessarily expose thousands of individuals to frequent colonoscopy.…”
mentioning
confidence: 80%
“…4 Therefore, it is of great importance to investigate whether these criteria indeed identify those patients that need strict surveillance. With great interest we read the article by Egoavil et al, 5 who assessed the risk of CRC in patients with SPS, as compared with those who harbor multiple serrated polyps (MSP) but do not fulfill the WHO criteria. The authors conclude that patients with MSP(ie, >10 polyps of which 50% are serrated polyps) harbor the same risk of developing CRC as patients with SPS and should require the same follow-up as proposed for SPS patients, that is, annual or biannual colonoscopy.…”
mentioning
confidence: 99%
“…The current World Health Organization criteria are somewhat arbitrary. Interestingly, a Spanish group showed that patients with multiple serrated polyps (defined as ≥10 polyps throughout the colon, of which more than 50% were serrated) who did not meet the criteria for SPS had a similar risk of CRC with patients confirmed to have the syndrome. Further refinement of the diagnostic criteria is likely needed in the near future to identify high‐risk patients that will benefit from yearly surveillance.…”
mentioning
confidence: 99%